2014
DOI: 10.20870/oeno-one.2014.48.1.1653
|View full text |Cite
|
Sign up to set email alerts
|

<em>Grapevine fleck virus</em> (GFkV) elimination in a selected clone of <em>Vitis vinifera</em> L. cv. Manto Negro and its effects on photosynthesis

Abstract: <p style="text-align: justify;"><strong>Aims</strong>: The use of healthy propagating material is required to control grapevine viruses. The aim of this work was to eliminate <em>Grapevine fleck virus</em> (GFkV) from a Manto Negro clone, a local grapevine variety, in order to include this material in certification programs. Additionally, the effects of virus elimination on photosynthesis and related parameters were evaluated.</p><p style="text-align: justify;"><str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…() working with Grapevine rupestris stem pitting associated virus ( GRSPaV ), where warm temperatures were associated with low virus concentration. In addition, it has been pointed out that high temperatures in the field can act as natural thermotherapy, stopping virus replication (Valero et al ., ; Bota et al ., ). However, in this study it seems that changes observed in virus concentration were affected mainly by the temperature of the previous month to the sampling day.…”
Section: Discussionmentioning
confidence: 97%
“…() working with Grapevine rupestris stem pitting associated virus ( GRSPaV ), where warm temperatures were associated with low virus concentration. In addition, it has been pointed out that high temperatures in the field can act as natural thermotherapy, stopping virus replication (Valero et al ., ; Bota et al ., ). However, in this study it seems that changes observed in virus concentration were affected mainly by the temperature of the previous month to the sampling day.…”
Section: Discussionmentioning
confidence: 97%
“…When these treatments are compared with those of Rukarwa et al (2010) using conventional thermotherapy (32 °C for 8 h in darkness and/or at 36 °C for 16 h light for 4 wk), it is possible to verify that they did not completely eliminate SPCSV even when thermotherapy was combined with meristem cultivation. Similarly, Bota et al (2014), in their experiment to obtain virus-free Vitis vinifera L. tissues, determined the low effectiveness of thermotherapy (20%) using a thermal chamber at 37.5/34.0 ºC (day/night) for 40 d.…”
Section: Thermotherapymentioning
confidence: 99%
“…포도의 Grapvine fleck virus (GFkV)는 GLRaV-1, GLRaV-3 바이러스들과 더불어 포도 식물체의 체관에만 한정적으로 존재하는(phloem-limited) 바이러스로 접목감염을 통해서만 전염되며 종자로는 전염되지 않는다 (Hewitt et al 1972;Martelli 1993;Martelli et al 2002). GFkV는 지표식물인Vitis rupestris에 서 잎에 얼룩을 나타내는 것을 제외하곤 대부분의 Vitis 종 (species)에서 증상을 드러내지 않는 잠복 감염형태로 존재 하나 (Martelli et al 2002), 식물 생리학적 측면에서 (Bota et al 2014), 그리고, 대개 다른 포도 바이러스와 복합감염 되어 있 을 경우에 생산량과 과실품질 측면에 부정적인 영향을 끼친 다고 하였다 (Cretazzo et al 2010a;Komar et al 2007;Kovacs et al 2001). GFkV는 세계적으로 감염분포가 매우 넓으며, 그 감 염이 지속적으로 보고되고 있는 가운데 (Cretazzo et al 2010b;Fiore et al 2008;Kumar et al 2013;Poojari et al 2016), 우리나라 에서도 재배되고 있는 몇몇 품종에서 감염보고가 있었다 (Kim et al 2011;Jo et al 2017).…”
Section: 서 언unclassified
“…GFkV 제거 기술에 관한 보고는 상당히 적은데, 지금까지 알려진 보고로는 열처리 후 경정배양법 (Bota et al 2014), 화 학처리법 (Guta et al 2014)이 있었고, 경정조직 파편배양 (Barlass et al 1982;Habili et al 1992 (Fig. 2B).…”
Section: 서 언unclassified